Corrosion Behavior of a Motor-Driven Filter Pipeline in Seawater Using the Weight Loss Method: Effect of Temperature and Flow - Martin Fatah; Ahmad Pratama; Andhika Pramono (Universitas Nusantara PGRI Kediri, 2026)
Failure of a motor-driven filter pipeline was reported due to seawater-induced corrosion. The objective of this study was to investigate the corrosion behavior of the pipeline material in seawater under static and dynamic conditions at temperatures of 27, 40, 60, and 80°C using the weight-loss method. Surface characterization was performed using scanning electron microscopy coupled with energy-dispersive spectroscopy (SEM-EDS) and X-ray diffraction (XRD). At 80°C, both static and dynamic conditions exhibited corrosion rates approximately twice those observed at 27°C. SEM observations revealed the formation of a dense and adherent corrosion-product layer at 27°C. However, at 80°C, cleavage and cracking of the corrosion-product layer were observed, allowing corrosive species to diffuse more readily to the metal surface and thereby accelerating corrosion. XRD analysis confirmed that the corrosion products consisted primarily of Fe2O3 (hematite) and Fe3O4 (magnetite).